Implementation of Human Resources Information Systems in Industrial Revolution 4.0: Case Study of Sekolah Tinggi Pariwisata Bali Internasional - Kadek Ari Styawati; A.A.N. Eddy Supriyadinata Gorda (Journal of Business on Hospitality and Tourism, 2020)
The rapid development of information and communication technology offers solutions in effective and efficient organizational management. The implementation of information technology becomes an important aspect in the competition in the digital arena. This study aims to examine in-depth about how the application of HRIS in STPBI. The research results showed that the implementation of HRIS at STPBI is used as a strategic activity in optimizing HR functions. The transformation and implementation of HRIS has several supporting and inhibiting factors. These supporting and inhibiting factors are combined in the development of HR in line with the theoretical and literary concepts used in this study. Through integrated work synergies in the field of staffing, transparency and availability of information is very helpful in decision making. The implementation of HRIS at STPBI is based on the paradigm of a balance between supporting factors and inhibiting factors.